Digital transformation of retail banking in Morocco: proposed model - EL HAOUA , Younes; MOUTAHADDIB , Aziz (Revue Internationale des Sciences de Gestion, 2023)
Given that our research based on a very meticulous documentary study, we have used dozens of reports to be able to draw the most probable conclusions to confirm or refute our research hypotheses. Twenty-seven annual reports were used, including 17 annual reports on banking supervision, and 10 annual reports on systems and means of payment and their monitoring, covering the period from 2004 to 2020. The objective of this research is to propose a targeted business model to ensure digital transformation for retail banks. Indeed, digitalization can become a key success factor with the main objective is optimising companies’ business processes: through the implementation of a business model whose priority (i) the quality of the product or service, (ii) cost control and (iii) real-time availability. Ensuring the digital transformation of Moroccan retail banking means: (1) being able to compete with new entrants; (2) maintaining and improving its market share; (3) ensuring performance.